Presnya: Territory of Innovations in Children Healthcare - Larisa E. Gorelova; Vera N. Shelkova (Вопросы современной педиатрии)
This article covers the history of children healthcare development in Presnensky district of Moscow. Social projects of Prokhorov Trekhgornaya manufactory, activities of Sofia Children’s Hospital, public charitable organizations, and city authorities together have created unique environment in the region for the successful implementation of innovations in children healthcare in the beginning of the 20 century. Pediatric medical and diagnostic technologies developed at Presnya were fully developed and created the basis for the Soviet children healthcare system. The Union of Pediatricians of Russia Forums have been held in Presnya since 1994. They continue the tradition of innovative development of children healthcare in Russian pediatrics. This article provides new data on the activities of distinguished Russian pediatricians G.N. Speransky and D.E. Gorokhov.